Uji Aktivitas Antijamur Fraksi N-Heksana, Etil Asetat, dan Air Ekstrak Metanol Kulit Batang Jambu Mete (Anacardium occidentale L.) Terhadap Candida albicans ATCC 10231 - Destik wulandari (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2023)
The bark of cashew nuts (Anacardium occidentale L.) contains compounds such as alkaloids, flavonoids, tannins and saponins which have the potential to inhibit the growth of fungi. The purpose of this study was to determine the antifungal activity of the extract, the n-hexane fraction, ethyl acetate, water and to determine the Minimum Inhibitory Concentration (MIC) and Minimum Killing Concentration (MBC) of the most active fractions of the methanol extract of cashew nut bark against the fungus Candida albicans ATCC 10231.